Effect of Combination of Follicle Size, FSH and Cysteamine on In Vitro Production of Sheep Embryos - Omar Mardenli; Mahdi Saleh Mohammad; Ahmad Yaser Alolo (Jurnal Ilmu Ternak dan Veteriner, 2020)
The participatory relationship among the follicle size, follicle stimulating hormone (FSH), and cysteamine (antioxidant agent) contribute to the production of embryos characterized by abundance and good quality. The aim of this study was to evaluate the efficacy of FSH, cysteamine and follicle size on in vitro embryo production of Awassi sheep oocytes. Follicles sizes were determined into two groups: small follicles (1-2 mm) and large follicles (> 2 mm). Oocytes were matured across two increasingly shared levels of FSH and cysteamine: A (40 ng/ml + 50 μM) and B (60 ng/ml + 100 μM). Results of the bilateral interaction showed significant differences across the follicle size (large follicles group) and the maturation treatment (B medium) in the rates of fertilization (highest value: 67.51%; p= 0.02), cleavage (highest value: 65.41%; p= 0.01), 2-16 cell stage (lowest value: 2.29%; p= 0.0001), blastocyst stage (highest value: 44.82%; p= 0.04), down to morula stage arrest (lowest value: 55.17%; p= 0.04) and Type I embryos (highest value: 52.87%; p= 0.03). Likewise, matured oocytes of small follicles group (B medium) attained the highest rate of morula stage (56.60%; p= 0.03). No significant differences were observed in Type II and Type III embryos. In order to obtain high yields of good quality embryos, it is advised to add FSH and cysteamine with levels of 60 ng/ml and 100 μM respectively to maturation medium of ovine oocytes obtained from follicles with a diameter > 2 mm.